Transitivity Analysis of W. H. Auden’s Poem “In Memory of W. B. Yeast” - Farooq, Hamna; Akhter, Nasreen; Khan, Ummi Farwa; Tariq, Somia (Pakistan Journal of Humanities and Social Sciences, 2024)
This paper presents the transitivity analysis of W. H. Auden’s poem “In Memory of W. B. Yeats” to describe the process types, participants' functions, and the circumstantial elements that characterize the text of the poem. The study also aims to explain the meaning of the text as to how it is created using experiential metafunction. This is the qualitative descriptive and quantitative study of the text; the clause is taken as the unit of analysis; the quantitative part of the study provides the frequency and percentage of the occurrences of process types, participants, and the circumstantial elements. The transitivity analysis is based on Halliday’s model of transitivity analysis presented by Thompson (2014). The findings are presented in the form of tables. The study found that process types that characterize text are material (52.6 %), relational (31.57 %), mental (8.77 %), verbal (5.26 %) while the behavioral one is (1.75 %). The dominant occurrence of the material and relational process shows that the writer has described the action and the relation of people after the death of Yeast as his death has changed nothing, the life goes on. The participants that characterize the text of the poem include actor (29.16 %), goal (13.88 %), carrier (18.05 %), attribute (13.88 %) as the dominant participants other are few. The circumstantial elements in the text are location (37.5 %), manner (32.14 %), contingence (21.42 %), extent, cause, accompaniment, and role, the dominant occurrence of location, manner, and contingence show the loss of poet has not changed the situation or the circumstances and show how the writer is describing the situation.